Seed Morphology of Ruellieae Species (Acanthaceae) in Brazil and Its Taxonomic Implications - Freitas Azevedo, Igor Henrique [UNESP]; Rodrigues de Moraes, Pedro Luis [UNESP] (Amer Soc Plant Taxonomists, 2019)
Ruellieae is a highly diverse tribe of Acanthaceae in Brazil, and morphological studies of its seeds have revealed important information about the systematics of the tribe. We analyzed the seed morphology of Brazilian species of Ruellieae, using stereoscopic, light, and scanning electron microscopy. The best-sampled genus was Ruellia (53 species), followed by Dyschoriste (seven), and Hygrophila (three); including external groups, a total of 65 species of Ruellieae (68 of Acanthaceae) were sampled. We observed capsular fruits with explosive dehiscence, important for autochory, and discoid seeds covered by hygroscopic and mucilaginous trichomes. The characters most relevant to the taxonomy of the groups were fruit shape, number of ovules, and the distribution, shape, and number of rings on the seed trichomes, the latter two addressed here for the first time. Those characters proved useful for discriminating and characterizing the sampled genera within Ruellieae, and especially the infrageneric clades of Ruellia. Based on the morphological patterns observed, we provide a key for those taxa, and suggest the infrageneric placement of unclassified Ruellia species: R. hypericoides and Ruellia sp. 4 for the clade Ebracteolati s.l., Ruellia spp. 2 and 3 for R. inflata, Ruellia sp. 1 for Euruellia s.s., and R. anamariae for the clade Blechum. In a broader context, we corroborate the finding that partial loss of seed trichomes is exclusive to one of the two large lineages of Neotropical Ruellia (lineage II). The hygroscopic and mucilaginous trichomes of Ruellieae seeds play important roles in water retention, germination, protection, and secondary dispersal, and we discuss some aspects of secondary hydrochory and epizoochory on medium- and long-range dispersal of Ruellieae, including transatlantic distances.
Keywords: Dispersal; fruits; Ruellia; systematics